Integrated pest management capsule against codling moth on apple in Jammu and Kashmir - Rather, Bashir Ahmad; Ahmad, Sheikh Bilal (Indian Journal of Plant Protection, 2020)
Efforts were made to develop an integrated pest management capsule against codling moth during 2009 and 2010 in six major fruit growing areas in the kargil region. Different management strategies were implemented, which include pheromone traps for monitoring and mass trapping, three consecutive sprays with three different insecticides each and cultural practices like destruction of infested fruits and burlapping of tree trunks, during both the years of study. Application of different tools of pest management from biofix to overwintering of larvae yielded significant results in reducing the damage in comparison to control during both the years. The overall population of moths captured in pheromone traps was higher in the first year and the average captures of codling moth/trap/week were 7.73 and 6.52 during 2009 and 2010, respectively. The mean fruit injury during 2009 was recorded at 19.6 per cent against control at 70.7 per cent, whereas in 2010 it was recorded at 14.4 per cent against control at 67.2 per cent. The overall impact of the pest management module recorded significant reduction in pest infestation and consequently in codling moth fruit injury in comparison to control during both the years of study.